El hombre víctima de la violencia familiar en Colombia: ¿Una realidad silenciosa e in- visibilizada? (2017)
This article entitled “The male victim of family violence in Colombia: a silent and invisible reality?” addresses new conceptualizations regarding the victims of domestic violence related to the study of gender in Colombia, which allows us to show throughout the development of this article another perspective where women and men go from being the classic victim-victimizer subjects respectively, and the man is an invisible victim without the support of policies state public.